Meeting Internal and External Demands: The Challenge of Developing English Language Proficiency in an Australian University - Dunworth, Katie (Australian Universities Quality Agency, 2009)
As the largest university in Western Australia, with campuses in Malaysia and Singapore and transnational partners in seven countries in the region, Curtin University of Technology has a high percentage of students who come from backgrounds where English is not the main language of communication. This paper describes a project which was introduced in 2008 to address the English language development needs of that particular cohort of students. It comprised the introduction of an online English language assessment tool that would assist students to diagnose their language needs, an integrated approach to the provision of language development services, the introduction of an institution- wide framework for assessing language proficiency and the monitoring and review of Curtin University's English language gatekeeping requirements. Now in its second year, the project has not only addressed internally identified needs but has also assisted in aligning Curtin University with the 'Good Practice Principles for English Language Proficiency for International Students in Australian Universities', which were approved and released by DEEWR in March 2009.